Development of A Children Worth City Based on Collaborative Governance In Kediri City - Indasah Indasah; Herry Krismono; Heri Saputro (STRADA : Jurnal Ilmiah Kesehatan, 2020)
This study aimed to 1) map the main problems of children in the development and potentials that exist in the regions from the aspects of policies, institutions/organizations of children that can be developed; 2) developing a collaborative governance model in the development of child-friendly cities in the Kediri. This research method uses descriptive qualitative using primary and secondary data. The results of the study describe the occurrence of child problems including information facilities for children, age of marriage under 18 years due to pregnancy, lack of optimal functioning of the consultation agency for parents, lack of mechanisms for monitoring victims of violence against children, decreasing rates of exclusive breastfeeding, and the absence of paying the law of several agencies. The potential of regional policies in the form of regional regulations, the number of children's social institutions is a strong social capital physically and socially in building a collaborative model/partnership